Teknik Pengemasan Produk Usaha Mikro Kecil Menengah (UMKM) - Syukur, Agus; Puspita, Ratna; Fabrianto, Luky; Tsabitah, Aida Salma; Bilqis, Shahnaz Hafiza; Rahman, Dafih Okta (PT. Riset Press International, 2025)
Product packaging for Usaha Mikro Kecil Menengah (UMKM) is highly urgent as a marketing strategy that not only protects the product but also increases sales value, brand differentiation, and consumer trust. The purpose of this community service activity is to provide understanding and training in effective, functional, and aesthetic packaging techniques, in accordance with the principles of informative, environmentally friendly, and market-oriented design. The targeted output is to increase the ability of UMKM to design attractive and professional packaging, be able to compete in the modern market, and implement innovations such aseco-packagingand smart packaging through Quick Response/QR Code integration. It is hoped that through this assistance, UMKM can optimize the function of packaging as a promotional and product protection tool, while simultaneously increasing the competitiveness and economic value of their products.